Implementation of the Adiwiyata School Program at Kembaran Public Elementary School, Kembaran Subdistrict, Banyumas Regency, 2024 - Aulia Putri Febriyanti; Ariesta Amanda; Chamid Sutikno; Indah Ayu Permana Pribadi; Andi Zaelani (Journal of Contemporary Pedagogy and Learning Science, 2026)
This study examines the implementation of the Adiwiyata School Program at SD Negeri Kembaran, Kembaran District, Banyumas Regency, by applying George C. Edward III’s policy implementation framework, which consists of communication, resources, disposition, and bureaucratic structure. A descriptive qualitative approach was employed, with data collected through interviews, observations, and document analysis. The data were analyzed using data reduction, data display, and conclusion drawing, while data validity was ensured through source and method triangulation. The findings indicate that the Adiwiyata Program at SD Negeri Kembaran has been implemented relatively well and is integrated into both curricular and extracurricular activities. The program has successfully fostered students’ environmental awareness, reflected in daily habits such as maintaining classroom cleanliness, sorting waste, and reusing materials through recycling activities. The effectiveness of implementation is supported by strong communication among stakeholders, adequate supporting facilities, and the commitment of school leadership and teachers. However, several challenges remain, including limited human resources, uneven participation among school members, and suboptimal administrative management. Continuous improvement is therefore required to strengthen participation and ensure the sustainability of environmental education within the school.